Peer Conformity Shapes Bystander Responses to Verbal Bullying: A Case Study of Second-Grade Students - Rutanti, Salsa; Iskandar, Sofyan; Mustikaati, Wina (Indonesian Psychological Research, 2026)
Children witnessing verbal bullying do not respond uniformly. Some remain passive whereas others choose to defend victims. However, the psychological processes underlying these contrasting responses remain underexplored among younger elementary school children. This study explored how peer conformity and socio-emotional processes shape second-grade students' bystander intervention during naturally occurring verbal bullying. A descriptive qualitative case study was conducted in a second-grade classroom at an Indonesian elementary school. Data were collected through classroom observations, semi-structured interviews with the classroom teacher and vice principal for student affairs, and analysis of teachers' bullying incident records. Data were analyzed using the interactive model of Miles, Huberman, and Saldaña. The findings revealed that passive bystander responses were associated with peer conformity, classroom norms, and diffusion of responsibility, whereas defending behavior emerged through empathy, supportive teacher modelling, and positive classroom interactions. These findings demonstrate that children's bystander intervention is shaped by the interaction between socio-emotional competencies and peer-group processes rather than individual characteristics alone. This study provides context-specific evidence that advances the understanding of bystander intervention among younger elementary school children and informs culturally responsive bullying prevention strategies.